Optimasi Pengolahan Limbah Cair Textile Menggunakan Metode Sono-Fenton - Riza Rizkiah; Luciana Luciana (Sainteks: Jurnal Sain dan Teknik, 2022)
The textile and textile product (TPT) industry is one of the mainstay commodities that drive the economy in Indonesia. Export market opportunities are very open for this commodity, but the current problem is the waste generated from this industry. PT.Vonex is a textile industry with spinning and dyeing products. Textile liquid waste produced has a very concentrated color characteristic and when the dye enters the waters it can cover the surface of the water body so as to block sunlight from entering the waters. Textile wastewater treatment with the sono-Fenton method as DCA (Decolorizing Agent) can be used as an alternative choice in overcoming these problems. In this study, an analysis of the reduction of the dye was carried out by using variations in the concentration of Fenton's reagent and the length of sonication time. The variations in the concentration of Fenton's reagent used were 1:1, 2:1, 4:1, and 6:1 while the sonication time used variations of 10, 30, 60 and 90 minutes. The test results show that the use of Fenton's reagent assisted by ultrasonic waves (sonication) in textile wastewater treatment can reduce the levels of color values, pH, COD, BOD, and TSS. The results showed that the variation of Fenton reagent concentration 1:1 with a sonication time of 30 minutes was the optimum condition with a percentage decrease in color value of 99.61%, a decrease in pH value of 68.94%, a decrease in COD value of 90.64%, a decrease in BOD levels by 97.48%, and a decrease in TSS levels by 91.28%.